2020
DOI: 10.1007/s10974-020-09584-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxin-induced skeletal muscle injury elicits profound changes in anabolic and stress signaling, and muscle fiber type composition

Abstract: To improve muscle healing upon injury, it is of importance to understand the interplay of key signaling pathways during muscle regeneration. To study this, mice were injected with cardiotoxin (CTX) or PBS in the Tibialis Anterior muscle and were sacrificed 2, 5 and 12 days upon injection. The time points represent different phases of the regeneration process, i.e. destruction, repair and remodeling, respectively. Two days upon CTX-injection, p-mTORC1 signaling and stress markers such as BiP and p-ERK1/2 were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 65 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…Protein extraction and western blot analysis. As previously described 3,22,38 , frozen skeletal muscle tissue (15-20 mg) was homogenized (4 × 20 s) in ice-cold lysis buffer (1/10 w/v; 50 mM Tris-HCl, pH 7.0; 270 mM sucrose; 5 mM EGTA; 1 mM EDTA; 1 mM sodium orthovanadate; 50 mM glycerophosphate; 5 mM sodium pyrophosphate; 50 mM sodium fluoride; 1 mM dithiothreitol; 0.1% Triton X-100; and a complete protease inhibitor tablet) using the FastPrep (MP Biomedicals, Santa Ana, CA). The obtained homogenates were centrifuged at 10,000g (20 min at 4 °C) and the supernatant was stored at − 80 °C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein extraction and western blot analysis. As previously described 3,22,38 , frozen skeletal muscle tissue (15-20 mg) was homogenized (4 × 20 s) in ice-cold lysis buffer (1/10 w/v; 50 mM Tris-HCl, pH 7.0; 270 mM sucrose; 5 mM EGTA; 1 mM EDTA; 1 mM sodium orthovanadate; 50 mM glycerophosphate; 5 mM sodium pyrophosphate; 50 mM sodium fluoride; 1 mM dithiothreitol; 0.1% Triton X-100; and a complete protease inhibitor tablet) using the FastPrep (MP Biomedicals, Santa Ana, CA). The obtained homogenates were centrifuged at 10,000g (20 min at 4 °C) and the supernatant was stored at − 80 °C.…”
Section: Discussionmentioning
confidence: 99%
“…LC3b). Unpublished data from our lab showed that CB 2 was downregulated during muscle atrophying conditions such as unloading and CTX-induced injury 22 in mice (Supplementary Figure 1 ). Others demonstrated that CB 2 agonism improved, whereas CB 2 antagonism impaired, muscle regeneration 23 – 25 .…”
Section: Introductionmentioning
confidence: 97%
“…This suggests that measuring MPS does not necessarily reflect net protein accrual, but rather the remodeling state of muscle. In agreement with this, it has been shown in rodents that MPS and associated anabolic signals can be increased in scenarios where overall muscle mass is lost rather than gained [74][75][76][77]. Indeed, pre-clinical and clinical studies suggest that the amount of muscle damage in response to RE might be more pronounced in older compared to younger individuals [56,78].…”
Section: Difference In Recovery From Resistance Exercise In Aged Musclesmentioning
confidence: 59%
“…Despite this, it is possible that inhibiting wild-type p53 had a negative effect on autophagy that contributed to muscle loss in our study. Overall, recent reports indicate that putative dissociations between anabolic signaling, protein synthesis and muscle mass may be a common phenomenon in various types of muscle wasting [ 69 , 70 , 77 79 ], illustrating the difficulty in relating transient processes like molecular signaling to muscle protein turnover and changes in the phenotype.…”
Section: Discussionmentioning
confidence: 99%